1997
DOI: 10.1001/jama.1997.03550160069041
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Age, Sex, and Ethnicity on the Association Between Apolipoprotein E Genotype and Alzheimer Disease

Abstract: The APOE epsilon4 allele represents a major risk factor for AD in all ethnic groups studied, across all ages between 40 and 90 years, and in both men and women. The association between APOE epsilon4 and AD in African Americans requires clarification, and the attenuated effect of APOE epsilon4 in Hispanics should be investigated further.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

143
2,043
23
25

Year Published

1999
1999
2018
2018

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 3,672 publications
(2,234 citation statements)
references
References 70 publications
143
2,043
23
25
Order By: Relevance
“…Thus, any cognitive and neural changes associated with ApoE-ɛ4 in individuals without dementia may be less reliably linked to AD than will similarly measured changes in clinically diagnosed AD patients. Nevertheless, a meta-analysis of more than 15,000 cases confirmed the importance of ApoE as a major susceptibility gene for AD at all ages (including as young as 40) and in all ethnic groups (Farrer et al, 1997). Studies of cognitive function in individuals without dementia who have the ApoE-ɛ4 gene may therefore provide important clues to the precursors of AD.…”
Section: Apoe As a Genetic Risk Factormentioning
confidence: 99%
“…Thus, any cognitive and neural changes associated with ApoE-ɛ4 in individuals without dementia may be less reliably linked to AD than will similarly measured changes in clinically diagnosed AD patients. Nevertheless, a meta-analysis of more than 15,000 cases confirmed the importance of ApoE as a major susceptibility gene for AD at all ages (including as young as 40) and in all ethnic groups (Farrer et al, 1997). Studies of cognitive function in individuals without dementia who have the ApoE-ɛ4 gene may therefore provide important clues to the precursors of AD.…”
Section: Apoe As a Genetic Risk Factormentioning
confidence: 99%
“…Among the three major isoforms of ApoE (e2, e3, and e4), the e4 allele has been reported to increase an individual's risk of developing AD, and decrease age of disease onset, in proportion to the number of e4 alleles present (Corder et al, 1993;Farrer et al, 1997). The search for phenotypic correlates of e4 has included neuropathological studies of the rate of b-amyloid (Ab) deposition Nagy et al, 1995;Norrman et al, 1995;Gomez-Isla et al, 1996), neurofibrillary tangle formation Nagy et al, 1995;Norrman et al, 1995;Gomez-Isla et al, 1996), cholinergic markers (Poirier et al, 1995;Soininen et al, 1995), and medial temporal lobe atrophy (Lehtovirta et al, 1996b;Hashimoto et al, 2001;Basso et al, in press).…”
Section: Introductionmentioning
confidence: 99%
“…ApoE4 has been identified as a risk factor for Alzheimer's Disease (AD), particularly in women, when compared to apoE3 [6]. Hartman and colleagues showed that 11-14 month-old transgenic male mice expressing human apoE4 in astrocytes under control of the glial fibrillary acidic protein (GFAP) promoter showed impairments in radial arm maze performance when compared to wild-type and mouse apoE deficient mice (Apoe −/− ) [9].…”
mentioning
confidence: 99%